IMRT and RapidArc commissioning of a TrueBeam linear accelerator using TG‐119 protocol cases. (8th September 2014) - Wen, Ning; Zhao, Bo; Kim, Jinkoo; Chin‐Snyder, Karen; Bellon, Maria; Glide‐Hurst, Carri; Barton, Kenneth; Chen, Daiquan; Chetty, Indrin J.
Abstract : The purpose of this study is to evaluate the overall accuracy of intensity‐modulated radiation therapy (IMRT) and RapidArc delivery using both flattening filter (FF) and flattening filter‐free (FFF) modalities based on test cases developed by AAPM Task Group 119. Institutional confidence limits (CLs) were established as the baseline for patient specific treatment plan quality assurance (QA). The effects of gantry range, gantry speed, leaf speed, dose rate, as well as the capability to capture intentional errors, were evaluated by measuring a series of Picket Fence (PF) tests using the electronic portal imaging device (EPID) and EBT3 films. Both IMRT and RapidArc plans were created in a Solid Water phantom ( 30   ×   30   ×   15   cm 3 ) for the TG‐119 test cases representative of normal clinical treatment sites for all five photon energies (6X, 10X, 15X, 6X‐FFF, 10X‐FFF) and the Exact IGRT couch was included in the dose calculation. One high‐dose point in the PTV and one low‐dose point in the avoidance structure were measured with an ion chamber in each case for each energy. Similarly, two GAFCHROMIC EBT3 films were placed in the coronal planes to measure planar dose distributions in both high‐ and low‐dose regions. The confidence limit was set to have 95% of the measured data fall within the tolerance. The mean of the absolute dose deviation for variable dose rate and gantry speed during RapidArc delivery was within 0.5% for all energies. The corresponding results for leaf speed tests were all within 0.4%. The combinations of dynamic leaf gap (DLG) and MLC transmission factor were optimized based on the ion chamber measurement results of RapidArc delivery for each energy. The average 95% CLs for the high‐dose point in the PTV were 0.030   ±   0.007 (range, 0.022–0.038) for the IMRT plans and 0.029   ±   0.011 (range, 0.016–0.043) for the RapidArc plans. For low‐point dose in the avoidance structures, the CLs were 0.029   ±   0.006 (range, 0.024–0.039) for the IMRT plans and 0.027   ±   0.013 (range, 0.017–0.047) for the RapidArc plans. The average 95% CLs using 3%/3 mm gamma criteria in the high‐dose region were 5.9   ±   2.7 (range, 1.4–8.6) and 3.9   ±   2.9 (range, 1.5–8.8) for IMRT and RapidArc plans, respectively. The average 95% CLs in the low‐dose region were 5.3   ±   2.6 (range, 1.2–7.4) and 3.7   ±   2.8 (range, 1.8–8.3) for IMRT and RapidArc plans, respectively. Based on ion chamber, as well as film measurements, we have established CLs values to ensure the high precision of IMRT and RapidArc delivery for both FF and FFF modalities. PACS number: 87